State nutrition profile: Chandigarh - Madhusudan, Aditya; Singh, Sudhir K.; Sarwal, Rakesh; Bhatia, Neena; Johnston, Robert; Joe, William; Sarswat, Esha; Menon, Purnima; Nguyen, Phuong Hong (International Food Policy Research Institute, 2022)
This Data Note describes the trends for a set of key nutrition and health outcomes, determinants, and coverage of interventions. The findings are based on estimates using unit-level data, data from national and state reports from the National Family Health Survey (NFHS)-3 (2005-2006) and NFHS-4 (2015-2016), and data from state factsheets and reports from NFHS-5 (2019-2021). In addition to standard prevalence-based analyses, this Data Note includes headcount-based analyses aligned to the POSHAN Abhiyaan monitoring framework to provide evidence that helps identify priority districts and number of districts in the state with public health concern as per the WHO guidelines. The Data Note includes a color-coded dashboard to compare the coverage of nutrition interventions across all the districts in the state. It concludes with key takeaways for children, women, and men, and identifies areas where the state has potential to improve.